Rituximab versus cyclophosphamide in ANCA-associated renal vasculitis: 2-year results of a randomised trial - Jones, Rachel B; Furuta, Shunsuke; Tervaert, Jan Willem Cohen; Hauser, Thomas; Luqmani, Raashid; Morgan, Matthew D; Peh, Chen Au; Savage, Caroline O; Segelmark, Marten; Tesar, Vladimir; van Paassen, Pieter; Walsh, Michael; et al. (Annals of the rheumatic diseases, 2015)
OBJECTIVES: The RITUXVAS trial reported similar remission induction rates and safety between rituximab and cyclophosphamide based regimens for antineutrophil cytoplasm antibody (ANCA)-associated vasculitis at 12 months; however, immunosuppression maintenance requirements and longer-term outcomes after rituximab in ANCA-associated renal vasculitis are unknown. METHODS: Forty-four patients with newly diagnosed ANCA-associated vasculitis and renal involvement were randomised, 3:1, to glucocorticoids plus either rituximab (375 mg/m(2)/week×4) with two intravenous cyclophosphamide pulses (n=33, rituximab group), or intravenous cyclophosphamide for 3-6 months followed by azathioprine (n=11, control group). RESULTS: The primary end point at 24 months was a composite of death, end-stage renal disease and relapse, which occurred in 14/33 in the rituximab group (42%) and 4/11 in the control group (36%) (p=1.00). After remission induction treatment all patients in the rituximab group achieved complete B cell depletion and during subsequent follow-up, 23/33 (70%) had B cell return. Relapses occurred in seven in the rituximab group (21%) and two in the control group (18%) (p=1.00). All relapses in the rituximab group occurred after B cell return. CONCLUSIONS: At 24 months, rates of the composite outcome of death, end-stage renal disease and relapse did not differ between groups. In the rituximab group, B cell return was associated with relapse. TRIAL REGISTRATION NUMBER: ISRCTN28528813.
Keywords: Antibodies, Monoclonal, Murine-Derived; Kidney Failure, Chronic; ANCA-asociované vaskulitidy; granulomatóza s polyangiitidou; Humans; Lymphocyte Count; lidé středního věku; Disease Progression; Glucocorticoids; Female; Aged; azathioprin; Granulomatosis with Polyangiitis; senioři; lidé; chronická renální insuficience; přežití bez známek nemoci; imunosupresiva; B-lymfocyty; myší monoklonální protilátky; Immunosuppressive Agents; Azathioprine; mikroskopická polyangiitida; ženské pohlaví; chronické selhání ledvin; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; Male; Middle Aged; Microscopic Polyangiitis; B-Lymphocytes; glukokortikoidy; Cyclophosphamide; počet lymfocytů; Disease-Free Survival; progrese nemoci; mužské pohlaví; Renal Insufficiency, Chronic; kombinovaná farmakoterapie; cyklofosfamid; Drug Therapy, Combination